A Comprehensive Cervical Cancer Profile in Nairobi County in Between 2015 and 2019 - Langat, Anne Chepkemboi; Tanui, Evans (European Journal of Applied Sciences, 2024)
Cervical cancer is the most prevalent cause of cancer-related deaths and morbidity worldwide that is the most common in women aged 45-60, with a disproportional burden in low- and middle-income countries compared to high-income countries. The high illness burden in resource-limited settings is attributed to insufficient knowledge of disease prevention and the lack of organized screening programs. Low middle income countries account for 80% of cervical cancer cases globally. Cervical cancer has a global incidence rate of 14 per 100,000 women. The present study delves to determine the Prevalence of cervical cancer in Nairobi county, to examine the age standard rates of cervical cancer and to determine the survival rates of cervical cancer patients. The study utilized retrospective design where patient records were reviewed to obtain data of Nairobi county women residents who sought medical attention from health care facilities due cervical cancer between the period of 2015-2019. Structured questionnaire obtained from the Nairobi county Abstract form at cancer registry (KEMRI).The data was analyzed using SPSS version 25 and can Reg 5. Descriptive statistics were utilized .The Results revealed that the mean affected age is 49.53 years. Most patients were diagnosed at stage 11 at 19.61%.Radiotherapy was the most preferred form of treatment at 46.75%.The survival rate was at 80.52%..Cervical cancer is considered the most common cancer in women. It is recommended that creating awareness can alter the trajectory of the cervical cancer orientation; training practitioners on high index cancer detection, early screening and adjustments on government policies can increase the survival rate. Moreover, HPV vaccination can prevent growth of malignant cervical cancer cells.